Ligand induction of a transcriptionally active thyroid hormone receptor coactivator complex. - Joseph D. Fondell; Hui Ge; Robert G. Roeder (1996)
Transcriptional regulation by nuclear hormone receptors is thought to involve interactions with putative cofactors that may potentiate receptor function. Here we show that human thyroid hormone receptor alpha purified from HeLa cells grown in the presence of thyroid hormone (T3) is associated with a group of distinct nuclear proteins termed thyroid hormone receptor-associated proteins (TRAPs). In an in vitro system reconstituted with general initiation factors and cofactors (and in the absence of added T3), the "liganded" thyroid hormone receptor (TR)/TRAP complex markedly activates transcription from a promoter template containing T3-response elements. Moreover, whereas the retinoid X receptor is not detected in the TR/TRAP complex, its presence is required for the function of the complex. In contrast, human thyroid hormone receptor alpha purified from cells grown in the absence of T3 lacks the TRAPs and effects only a low level of activation that is dependent on added ligand. These findings demonstrate the ligand-dependent in vivo formation of a transcriptionally active TR-multisubunit protein complex and suggest a role for TRAPs as positive coactivators for gene-specific transcriptional activation.